Relationship between HbA1c Levels with eGFR and Blood Pressure in Type 2 Diabetes Mellitus Patients in the Department of Internal Medicine Dr. Soetomo General Hospital Surabaya - Sugondo, Alexander Tikara; Ardiany, Deasy; Nuswantoro, Djohar; Notopuro, Pulus Budiono (Biomolecular and Health Science Journal, 2019)
Introduction: Diabetes mellitus is a non-transmitted pandemic disease which had spreaded on a global scale. The prevalence of diabetes mellitus in the world according to the International Diabetes Federation (IDF) is 1.9% and diabetes mellitus is ranked seventh as the cause of death in the world, around 95% in the world is type 2 diabetes mellitus. According to Riset Kesehatan Dasar (Riskesdas) in 2013, the prevalence of diabetes mellitus in Indonesia is 6,9%. Type 2 diabetes mellitus that is not well controlled will increase the risk of chronic complications, both microangiopathies such as nephropathy, and macroangiopathy such as hypertension. The aim of the study was to determine correlation between HbA1c levels with eGFR (Estimated Glomerulus Filtration Rate) and blood pressure (systolic and diastolic).Methods: An analytic observational cross-sectional study, collecting the data from 94 patients with type 2 diabetes mellitus, Dr. Soetomo General Hospital, Surabaya, from January to May 2018. The variables were collected from patient's medical records. Analysis using Spearman's Rank Correlation test. To determine normality of the data, we use Kolmogorov-smirnov test.Results: The results showed that there are 134 (57,8%) patients with type 2 diabetes mellitus are female more than male. Patients with greater than or equal to 45 years old were 203 (87,5%) patients, more than under 45 years old. The correlation test showed that there was no significant correlation between HbA1c and systolic blood pressure (r=-0,127; p=0,054). Also there was no significant correlation between HbA1c and diastolic blood pressure (r=-0,111; p=0,093). Analysis on other factor showed a significant correlation between HbA1c and eGFR (r=0.341; p=0.000).Conclusion: There was no significant correlation between HbA1c and systolic blood pressure, also there was no significant correlation between HbA1c and diastolic blood pressure. But, there was a significant correlation between HbA1c and eGFR. This is because the data retrieval does not consider the drug consumption and therapy that has been done by the patient, as well as examination of HbA1c, serum creatinine eGFR, and blood pressure not at the same time.